PROFESSIONAL STRESS IN SOCIAL WORKERS AND PSYCHOLOGISTS EMPLOYED IN THE FIELD OF SOCIAL CARE AND HEALTH - Trajkov, Ivan; Serafimovska, Eleonora; Markovikj, Marijana (Institute for Sociological, Political and Juridical Research, 2015)
Professional stress of persons working in helping professions (social workers, psychologists) is insufficiently researched in our country, which reduces the possibility of taking measures to prevent occupational “burn out”. On the other hand, the significant socio-economic and political changes in the country have led to an increase in the number of people who face social risks, which inevitably increased the workload of persons from helping professions. In order to establish the situation with professional stress in these occupations in a time span of ten years were carried out two identical surveys. Two instruments were used: list of general data and Scale for measuring professional stress (Weissman, 1996). The obtained data showed an increase in the number of professionals (social workers and psychologists) with high level of professional stress, risk of “burn out” as a result of the increased volume of work engagement. The results of this study could be used in planning future research but also as a basis for planning and preparing programs for rehabilitation and prevention of occupational stress in individuals working in helping professions.
Keywords: professional stress, burn out, helping professions, social risk